Public education, technological change and economic prosperity: semi-endogenous growth revisited - Klaus Prettner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
We introduce publicly funded education into R&D based economic growth theory. Our framework allows us to i) explicitly describe a realistic process of human capital accumulation within these types of growth models, ii) reconcile semi-endogenous growth theory with the empirical evidence on the relationship between economic development and population growth, iii) revise the policy invariance result of semi-endogenous growth frameworks. In particular, we show that the model supports a negative (positive) association between economic growth and population growth if the education sector is well (badly) developed and that changes of public investments into education crucially affect the long-run balanced growth path.
Keywords: J24; O11; O41; 330